A comparison of digital health competence and associated factors among Czech nurses using online versus paper-based data collection methods: a cross-sectional study. - Mandysová, Petra; Mikkonen, Kristina; Tomietto, Marco; Jarva, Erika; Červenková, Zuzana; Pekara, Jaroslav; Krause, Martin (Central European Journal of Nursing & Midwifery, 2025)
Aim: To compare digital health competence (DHC) and associated factors among Czech nurses from various healthcare settings, using online versus paper-based data collection methods. Design: A cross-sectional survey. Methods: Data were collected from October 2023 to July 2024. The survey included demographic and professional data, along with two DHC instruments: DigiHealthCom and DigiComInf, translated from English to Czech. Descriptive analysis, likelihood ratio (LR), χ² and Fisher's exact tests, and the Mann-Whitney U test were used to analyze the data. Results: The survey was fully completed by 263 nurses. Significant differences were observed between the paper-based and online subgroups in most demographic and professional variables, with large effect sizes for educational level (Z = -7.436; p < 0.001) and frequency of patient interactions (Z = -6.243; p < 0.001). Overall, most DHC items received favorable ratings for digitalization and associated factors. While subjectively perceived DHC differed significantly between the subgroups in most factors, the effect sizes of these differences were not large. Conclusion: Although the level of DHC was favorable, further research is warranted due to extensive missing data, which may be the result of limited experience and a lack of established opinions on certain items.